The Relationship Between Linguistic Anxiety and Lexical Search Speed in Official Communication - Munawaroh, Siti; Salsabila, Irma Nuraeni (Sekolah Tinggi Agama Islam Kuningan, 2025)
This study highlights the relationship between linguistic anxiety and lexical search speed in formal communication. The background of the study shows that formal situations often trigger anxiety, which results in slow vocabulary selection and long speech pauses. Qualitative methods were used through observation, interviews, and thematic analysis of employees of government agencies and multinational companies. Results showed a correlation between high levels of anxiety and decreased word search efficiency, hindering communication fluency. The practical implication is the importance of integrated anxiety management and language training, so that individuals can be more confident and effective when dealing with the demands of formality.